Emergency department-initiated tobacco control: a randomised controlled trial in an inner city university hospital. Issue 4 (14th June 2009) - Neuner, B; Weiss-Gerlach, E; Miller, P; Martus, P; Hesse, D; Spies, C
Abstract : Objectives: Emergency department (ED) patients show high smoking rates. The effects of ED-initiated tobacco control (ETC) on 7-day abstinence at 12 months were investigated. Methods: A randomised controlled intention-to-treat trial (trials registry no.: ISRCTN41527831) was conducted with 1044 patients in an urban ED. ETC consisted of on-site counselling plus up to four telephone booster sessions. Controls received usual care. Analysis was by logistic regression. Results: In all, 630 (60.7%) participants were males, the median age was 30 years (range 18–81) and the median smoking intensity was 15 (range 1–60) cigarettes per day. Overall, 580 study participants (55.6%) were unmotivated, 331 (31.7%) were ambivalent and 133 (12.7%) were motivated smokers. ETC (median time 30 (range 1–99) min) was administered to 472 (91.7% out of 515) randomised study participants. At follow-up, 685 study participants (65.6% of 1044) could be contacted. In the ETC group, 73 out of 515 (14.2%) in the ETC group were abstinent, whereas 60 out of 529 (11.3%) controls were abstinent (OR adjusted for age and gender = 1.31 (95% CI 0.91 to 1.89, p = 0.15). Stratified for motivation to change behaviour, the adjusted ORs for ETC versus usual care were OR = 1.00 (95% CI 0.57 to 1.76) in unmotivated smokers, respectively OR = 1.37 (95% CI 0.73 to 2.58) in ambivalent smokers and OR = 2.19 (95% CI 0.98 to 4.89) in motivated smokers, p for trend = 0.29. Conclusions: ETC, in the form of on-site counselling with up to four telephone booster sessions, showed no overall effect on tobacco abstinence after 12 months. A non-significant trend for a better performance of ETC in more motivated smokers was observed.